2022
DOI: 10.1002/adfm.202206912
|View full text |Cite
|
Sign up to set email alerts
|

Programming Shape Memory Hydrogel to a Pre‐Encoded Static Deformation toward Hierarchical Morphological Information Encryption

Abstract: Morphological information encryption such as gesture and sign language is a traditional but efficient way of information storage and communication. However, due to the limited deformability, almost all of the existing information encryption materials store and deliver information via the pattern or color changes on the 2D plane. Herein, a thermo and ion dual-responsive shape memory hydrogel containing short alkyl chains modified polyvinyl alcohol (PVA-C6) and polyacrylamide-co-polyacrylic acid [P(AAm-co-AAc)],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 48 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…Particularly, the applied electric field could redistribute its mobile ions that direct the migration of water molecules, therefore triggering the actuation (Figure 6e). Lu et al [195] prepared a 3D TFFA using thermo/ion dual-responsive hydrogel, showing great capabilities of shape fixing and morphing.…”
Section: D Tffas Based On Hydrogelsmentioning
confidence: 99%
“…Particularly, the applied electric field could redistribute its mobile ions that direct the migration of water molecules, therefore triggering the actuation (Figure 6e). Lu et al [195] prepared a 3D TFFA using thermo/ion dual-responsive hydrogel, showing great capabilities of shape fixing and morphing.…”
Section: D Tffas Based On Hydrogelsmentioning
confidence: 99%
“…Gao et al reported a lanthanide polyoxometalate-based luminescent hydrogel for encryption . Similarly, Lu et al reported a thermo and ion dual-responsive hydrogel for morphological information encryption . However, there is only a handful of literature available based on CPG materials for anticounterfeiting. Therefore, there is a wide open space for the design and development of CPG-based materials for anticounterfeiting applications.…”
Section: Introductionmentioning
confidence: 99%
“…Information security is of great significance in the development of enterprises, social stability, military security, and even personal daily life. Over the past few decades, a wide variety of technologies, including markering, holograms, magnetism, plasmonic labels, and luminescence, have been investigated for use in anticounterfeiting and information encryption. Among these technologies, luminescence has demonstrated great potential because of its timeliness, simplicity, multiencoding dimensions, and low cost. So far, diverse luminescent materials featuring photoluminescence (PL), thermoluminescence (TL), upconversion luminescence (UCL), downconversion luminescence (DCL), persistent luminescence (PersL), mechanoluminescence (ML), and photostimulated luminescence (PSL) have been widely developed for high-level encryption. However, most PL-based anticounterfeiting labels are easily falsified by certain alternatives due to their static luminescence color and intensity, single-emission mode, or simple design .…”
Section: Introductionmentioning
confidence: 99%